2017
DOI: 10.1073/pnas.1618819114
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of climate and fisheries drive ongoing declines in multiple albatross species

Abstract: Environmental and anthropogenic factors often drive population declines in top predators, but how their influences may combine remains unclear. Albatrosses are particularly threatened. They breed in fast-changing environments, and their extensive foraging ranges expose them to incidental mortality (bycatch) in multiple fisheries. The albatross community at South Georgia includes globally important populations of three species that have declined by 40-60% over the last 35 years. We used three steps to deeply un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 53 publications
3
100
0
2
Order By: Relevance
“…This is one of the few studies to examine sex-specific effects of environmental variation and fishing effort on survival rates in a marine vertebrate Martínez-Abraín et al, 2006;Olsson & Van der Jeugd, 2002). Although the canalization theory (Fay, Weimerskirch, Delord, & Barbraud, 2015;Gaillard & Yoccoz, 2003) predicts a stronger buffering against environmental variability in adult survival (Jenouvrier, Barbraud, Cazelles, & Weimerskirch, 2005;Pardo et al, 2017), which is the most sensitive vital rate to the population growth rate of large seabirds, we showed that the survival of giant petrels of one or both species was influenced by large-scale climatic indices, oceanographic characteristics, availability of fur seal carrion and fisheries. We found interspecific differences, and, as expected, both species showed sex-specific responses to environmental variability, highlighting the importance of considering such within-population variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is one of the few studies to examine sex-specific effects of environmental variation and fishing effort on survival rates in a marine vertebrate Martínez-Abraín et al, 2006;Olsson & Van der Jeugd, 2002). Although the canalization theory (Fay, Weimerskirch, Delord, & Barbraud, 2015;Gaillard & Yoccoz, 2003) predicts a stronger buffering against environmental variability in adult survival (Jenouvrier, Barbraud, Cazelles, & Weimerskirch, 2005;Pardo et al, 2017), which is the most sensitive vital rate to the population growth rate of large seabirds, we showed that the survival of giant petrels of one or both species was influenced by large-scale climatic indices, oceanographic characteristics, availability of fur seal carrion and fisheries. We found interspecific differences, and, as expected, both species showed sex-specific responses to environmental variability, highlighting the importance of considering such within-population variation.…”
Section: Discussionmentioning
confidence: 99%
“…At‐sea distributions of non‐breeding birds were mapped for each giant petrel species, based on 130 and 126 tracks of different individuals of NGP and SGP, respectively, fitted with Global Location Sensors (GLS loggers; British Antarctic Survey, Cambridge, UK) in summer 1999/2000 (Figure S2.1; based on data in González‐Solís et al, ). Subsequently, we extracted the data for the model covariates from all of the 5 × 5° cells within the 50% utilization distributions (UDs) for oceanographic characteristics (SST, NPP and wind components), as this was considered to reflect the conditions experienced in core areas, and the 90% UDs for trawl, demersal and pelagic longline fishing effort, which was considered to better reflect the potential encounters with fishing vessels (Pardo et al, ). Data on krill biomass and sea ice cover (SIC) were obtained from fixed sampling areas (see Appendix S2).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, recent increases in the foraging range and breeding success of wandering albatrosses are thought to have been mediated by strengthening winds in the Southern Ocean [22]. Similarly, variation in annual survival, breeding probability or breeding success of wandering albatross, black-browed Thalassarche melanophris and grey-headed albatross T. chrysostoma at South Georgia have been linked to changes in the wind regime [23], suggesting that ongoing global climate change may have major impacts on albatrosses, and pelagic seabirds in general. A necessary precursor to understanding and predicting how the wind affects the movements and, ultimately, the demography of seabirds is to quantify its effects on flight performance (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Incidental mortality from fisheries bycatch is a principle threat to seabird biodiversity, particularly for the Procelleriformes (albatrosses and petrels) (Croxall and Gales, 1998;Tuck et al, 2001;Cherel et al, 2017;Pardo et al, 2017). Fifteen out of 22 recognized species of albatrosses are currently threatened or endangered, of which three are critically endangered (IUCN, 2017).…”
Section: Introductionmentioning
confidence: 99%